Welfare State Policy Model as A Poverty Reduction Strategy in the West Sumatra Districts and Cities - Azwar Azwar Azwar; Emeraldy Chatra; Zuldesni Zuldesni (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
Poverty is one of the social problems that the government can never completely solve. As a result, other, more significant social issues arise and cause social vulnerability, such as conflict and crime. As a province that is experiencing rapid growth in the last ten years, the West Sumatra find difficulty to overcome the number of poor people in several districts and cities.  The research outcomes are the models and forms of social policy made by West Sumatra regencies and cities governments in improving the welfare of poor communities. It is also covering the constraints or obstacles to the implementation of social policy and the selection of welfare state models for the poor in some districts and municipalities of West Sumatra. This research is conducted qualitatively with a sociological approach that uses social perspective on searching and explaining social facts that happened to needy groups. Based on research conducted that the social policy model adopted by the government in responding to social problems in the districts and cities of West Sumatra reflects the welfare state model given to the poor. There is a strong relationship between the welfare state model and the form of social policy made by the government.